2019
DOI: 10.1002/est2.113
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer model of a particle energy storage‐based moving packed bed heat exchanger

Abstract: Moving packed bed particle/supercritical carbon dioxide (SCO 2 ) heat exchanger (MPBE) is a critical equipment to integrate particle thermal energy storage technology with SCO 2 power cycle block in the next-generation concentrated solar power plants. A predictive heat transfer model for designing and evaluation of shell and plate particle/SCO 2 moving packed bed heat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 32 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Particle flow simulation methods can be divided into the continuous method and the discrete method. At present, many scholars simplify the particle flow in the vertical channel as the plug flow [25], regard the particle flow as the continuous medium to simplify the design of MBHE [26] and explore the influence of relevant parameters [22]. When the particles move around a vertical smooth plate, it is feasible to treat the particles as a continuous medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle flow simulation methods can be divided into the continuous method and the discrete method. At present, many scholars simplify the particle flow in the vertical channel as the plug flow [25], regard the particle flow as the continuous medium to simplify the design of MBHE [26] and explore the influence of relevant parameters [22]. When the particles move around a vertical smooth plate, it is feasible to treat the particles as a continuous medium.…”
Section: Methodsmentioning
confidence: 99%
“…Nie et al [21] analyzed the effects of particles with different thermophysical properties on the performance of the directly irradiated solid particle solar receiver with semi-annular flow channels. Yin et al [22] found that increasing particle diameter and solid void ratio can reduce the total heat transfer coefficient, and the change of channel width has a great influence on the total heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The static model of a shell and plate particle-SCO 2 MPBE has been established in the author's former publication, with the intent to conduct a parameter analysis on the effects of solids properties, channel geometries on the performance of MPBE, as well as to compare the contributions of different thermal resistances. 24 Reasonable assumptions have been adopted; therefore, the energy functions of SCO 2 and solids have been simplified as a one-dimension ordinary differential equation and a two-dimension partial differential equation, respectively. The static model takes pressure drop, radiation, and property variations into consideration.…”
Section: Static Modelmentioning
confidence: 99%
“…Nevertheless, their model did not take radiation among solids, radiation between particles and the dividing wall into consideration, nor the pressure drop and relevant property variations. To ameliorate these vulnerabilities, Yin et al introduced the radiation and pressure drop submodels recently 24 . The findings came out that the convection resistance in the SCO 2 channel side ranks the maximum heat transfer resistance in specific thermal resistance and contributes a large part in total thermal resistance in most design‐point and off‐design cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation